The current state of DNA methylation biomarkers in self-collected liquid biopsies for the early detection of cervical cancer: a literature review - Elizabeth G. Sumiec; Zhe Yang Yim; Hannah Mohy-Eldin; Belinda Nedjai (Infectious Agents and Cancer)
Abstract Cervical cancer (CC) is a preventable disease and treatable cancer. Most of the new cases and deaths from CC occur in Low- and Middle-Income Countries (LMICs) due to cultural and systematic barriers leading to low CC screening uptake. In recent years, self-sampling has been proposed as a method to increase CC screening uptake and is slowly being implemented into screening programmes worldwide. Simultaneously, DNA methylation has been proposed as a novel biomarker that could be used for the triage of self-collected samples that test positive for high-risk types of Human Papillomavirus (HPV). In this paper, we conducted a literature review of studies assessing the efficacy of DNA methylation markers to detect Cervical Intraepithelial Neoplasia (CIN) in self-collected cervicovaginal swabs or urine (2019–2024). Our review showed that, of the available data, DNA methylation together with self-sampling could perform as well as cytology in the detection of CIN as well as improve uptake of CC screening and reduce loss to follow up, especially in LMICs. However, more data is still needed to understand which methylation tests are most efficacious. Future studies should assess the full potential of DNA methylation and self-sampling in large, diverse screening cohorts.